STEGANOGRAPHIC TRANSFORMATION METHOD WITH DETECTION OF STRUCTURAL DEPENDEN-CIES OF VIDEO CONTAINERS - Barannik, Volodymyr; Prokopenko, Rodion (Science-based technologies, 2026)
transmitted from robotic complexes. For this, selective processing is used. However, the problematic issue here is that with the increase in the complexity of video images, the number of segments whose information requires protection increases. There are losses in the compression level. The main reason for this is the destruction of dependencies used in the process of reducing redundancy. Hence, the relevant scientific and applied problem is related to increasing the level of confidentiality of video information for robotic platforms with achieving the required level of processing time. The article considers two approaches to solving the problem. The first approach concerns improving the quality of selective processing of video images. Another option is to organize the protection of video information during its compression. An option here may be the use of steganographic transformations. The special properties of steganographic transformations are shown. Firstly, the use of steganographic methods in complex information protection systems allows to increase the level of information confidentiality. Secondly, steganographic methods have the potential to reduce the impact on the destruction of compression-important dependencies. The article considers several directions for building steganographic information protection methods. Cases of building containers based on video content are presented. It is indicated that the most practically tested is the implementation of steganographic information embedding using least significant bit (LSB) methods. However, under the conditions of the required level of steganographic capacity, compression level losses occur. Hence, it is important to create alternative technologies for steganographic information hiding to the LSB method. The article presents the development of a method of steganographic transformations by taking into account dependencies in the structural space based on the modification of the adaptive P-basis. The advantage of the created steganographic system over existing approaches in terms of steganographic capacity in the conditions of the required resistance to visual attacks (attacks on the detection of the fact of embedded messages) is proven.